2022
DOI: 10.18280/ts.390123
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ensemble Bagging Classification Method for Breast Cancer Classification Using Machine Learning Techniques

Abstract: Breast cancer is observed as a dangerous disease type for women in the world. The clinical experts stated that early detection of cancer helps in saving lives. To detect cancer in the early stage, medical image processing is observed as an effective field. Medical Image processing with an appropriate classification mechanism improves accuracy and image resource with minimal processing time. To detect breast cancer several machine learning techniques are evolved for cancer classification. However, those machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Next, the researchers found that a bagging ensemble with attribute selection could be an applicable method to support software tools for predicting the efficient results of schizophrenia. Ponnaganti and Anitha [9] suggested an Ensemble Bagging Weighted Voting Classification (EBWvc) method for the categorization of breast cancer. The researchers comparatively evaluated five metrics, and their results showed an increased performance of the EBWvc method if compared to similar existing classification methods.…”
Section: Bagging Ensemblesmentioning
confidence: 99%
“…Next, the researchers found that a bagging ensemble with attribute selection could be an applicable method to support software tools for predicting the efficient results of schizophrenia. Ponnaganti and Anitha [9] suggested an Ensemble Bagging Weighted Voting Classification (EBWvc) method for the categorization of breast cancer. The researchers comparatively evaluated five metrics, and their results showed an increased performance of the EBWvc method if compared to similar existing classification methods.…”
Section: Bagging Ensemblesmentioning
confidence: 99%
“…The real input mammogram images were obtained from the universal available Image Analysis Society's database (MIAS). After the noise and artifact sources had been removed, the pectoral part of muscles from the image was removed by the seed growing technique such as contour growing, histogram thresholding and edge detection [7][8][9]. The defined method is perfect and completely computerized.…”
Section: Preprocessingmentioning
confidence: 99%
“…Almost all medical/diagnostic centers, however, are currently struggling to analyze the increasing volume of mammograms. Computer Aided Diagnosis (CAD) is more popular in diagnosing suspicious tumors in women's breasts with good results in terms of improved precision and accuracy [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their main goal was to aid in minimizing mistakes made when determining whether a breast tumour was malignant or not. For the classification of breast cancer, the paper [17] suggested an Ensemble Bagging Weighted Voting Classification (EBWvc). Initially, bagging is used for the obtained data to address overfit in machine learning.…”
Section: Introductionmentioning
confidence: 99%